TASAWUF SEBAGAI INTISARI AJARAN ISLAM DAN RELEVANSINYA TERHADAP KEHIDUPAN MASYARAKAT MODEREN - Asep Saepullah (Universitas Islam Negeri Imam Bonjol Padang, 2021)
There are at least two functions of religion in human life, namely as a norm and as a science. Islam is no exception, which has three aspects of Shari'ah, namely faith, Islam, and Ihsan. Faith and Islam are easy to explain and understand by most Muslims around the world, because they talk about monotheism and practical sciences. Like fiqh and other sciences. However, in the aspect of Ihsan related to Sufism, there are still few Muslims who are aware of the importance of this aspect. Without this aspect, it is difficult for Muslims to understand the teachings of Islam in kaffah, because it can be said that this aspect is the center of Islam other than monotheism or sharia. Another problem arose, when the 19th to 20th century thought patterns, known for their positivism, tended to reject the meaningless sciences of religion. From this pattern of thinking, modern society was born. Without going through monotheism, sharia, and compassion as the essence of Islamic teachings, it will be difficult for modern society to do good, prevent from evil, and draw closer to Allah swt. Therefore, the author tries to explain how the relevance between Sufism as the essence of Islamic teachings with the life of modern society through a descriptive-philosophical approach. Through this approach, the author concludes that Sufism as the essence of Islamic teachings is able to provide an indirect impact on modern society.